Several Different Origins of the ա /a/ Vowel-Final Imperative of Simple Verbs in the է/ի /ē/i/ Conjugation in Modern Armenian Dialects - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2025)
An attempt is made to show that the ա /a/ vowel-final imperative forms of simple verbs in the է/ի /ē/i/ (derived from Classical Armenian ե /e/ and ի /i/) conjugation in modern Armenian dialects have several origins. Specifically, a synchronic and diachronic analysis of the relevant evidence from modern Armenian dialects has allowed us to identify three main lines of development that have led to the appearance of the forms in question: 1) in some dialects (e.g., in the dialects of Agulis, Karčewan, and Kakʻavaberd) the form has resulted from the regular sound change of եա /ea/ to ա /a/; 2) in several subdialects within the dialect of Ararat, analogical influence from three high-frequency transitive verbs, namely, ասէլ /asēl/ “to say”, 2 sg. imp. ասա՛ /asa՛/ “say!”, ածէլ /acēl/ (originally meaning “to bring, to adduce! ”, later “to fill”), 2 sg. imp. ածա՛ /aca/ (originally meaning “bring!, adduce!”, later “fill!”), անէլ /anēl/ “to do”, 2 sg. imp. արա՛ /ara՛/ “do!”, is quite likely to have been responsible for the appearance of the form in question, with the verb ասէլ /asēl/ “to say” having played a pivotal role in this process; 3) in still other dialects (e.g., the dialects of Bayazet and Diadin, and the subdialect of Alaškert), a sound change from է /ē/ to ա /a/ appears to have occurred in the enclitic 3 sg. present form of the auxiliary verb եմ /em/, likely due to an articulatory weakening in muscular tension. Later, the vowel ա /a/ was analogically extended from the 3 sg. present form of the auxiliary verb to the 3 sg. optative of verbs in the ե /e/ conjugation, and from there to the 2 sg. imperative.